Tawakal Dalam Menuntut Ilmu - Martoyo Martoyo; Cinli Cinli (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2024)
Tawakal in Demanding Knowledge in the book of Ta'lim al-Muta'alim means surrendering to Allah SWT in seeking knowledge. This concept is associated with effort, not worrying, being patient, and using all the time to study. Tawakal does not mean abandoning physical efforts, but putting them within the framework of Allah's decree. In Imam Ghazali's perspective, tawakal must be done with knowledge as the main basis and the doors of tawakal are faith and tawhid. This type of journal research is classified into library research, which is research conducted in the library to collect and analyze data sourced from libraries, both in the form of books, documents and other library materials. Tawakal in studying according to the book of Ta'lim al-Muta'alim means surrendering to Allah SWT with effort, not worrying, being patient, and using all the time to study, and having an awareness of the importance of living hard and difficult and not being affected by worldly affairs.